The analysis of competing hypotheses and expert witness testimony: Counteracting adversarial allegiance in witness credibility assessments? - Jana Otzipka; Renate Volbert (PLoS ONE, 2026)
Cognitive biases, such as adversarial allegiance, can compromise expert witness evaluations and contribute to wrongful convictions. Therefore, the application of debiasing strategies is essential. The Analysis of Competing Hypotheses (ACH) has been proposed as a potential method to reduce such bias, although empirical support remains limited. The present study investigated the effectiveness of the ACH method in mitigating adversarial allegiance in a sample of mock expert witnesses for credibility assessments. In an online experiment, 159 participants with prior knowledge in credibility assessments reviewed a summary of a child sexual abuse case. Before reviewing the case material, participants were randomly assigned to one of three retaining party conditions: defense, accessory prosecution, or court. Next, half of the participants were instructed to apply the ACH method which includes the systematic comparison of alternative hypotheses within a matrix. Meanwhile the control group was instructed to follow the standard approach in credibility assessments in Germany, which includes the evaluation and falsification of alternative hypotheses, albeit in a less structured way than the ACH method. Outcomes were assessed using credibility ratings and an Evidence Score, the latter reflecting the extent to which participants weighed evidence in favor of their retaining party or evaluated information more evenly. No significant differences emerged in credibility ratings across conditions. However, adversarial allegiance was evident in the Evidence Score: defense-retained participants emphasized evidence undermining the statement’s credibility more than those retained by the accessory prosecution. At the same time, the application of the ACH method did not significantly influence credibility ratings or evidence selection. Overall, these findings suggest that the ACH method may have limited utility as a debiasing strategy in the context of credibility assessments and underscore the challenges of mitigating bias in forensic decision-making.